Developing an Optimization Algorithm for Solving Economic Dispatch Problem in Microgrids - Lotfiakbarabadi, Mohammad (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
In the power system, one of the remarkably popular and fundamental optimization problems is economic power dispatch. Economic dispatch in a classical form contains only thermal generators without considering network security constraints. However, other forms of this problem like economic emission dispatch are gaining more importance since minimization of emission is predominant from the environmental point of view. Moreover, integrating renewable sources comes with challenges due to the stochastic nature of them. In this study, a multi-objective algorithm is developed to deal with the problem of economic emission power dispatch integrated with solar, wind, and small-hydro unit. Lognormal, Weibull and Gumbel distribution for predicting the accessible power of solar, small hydro, and wind power is utilized respectively. For the goal of the study, some of the traditional generators are replaced in the structure of the IEEE 30-bus network, with different renewable units of energy. Voltage limitation, capacities of the transmission line, prohibited areas of operation for the thermal generator plants, and restriction of the system are also considered. Multi-objective real coded non-dominated sorting genetic algorithm II is enforced to the problem of this study while incorporating a decent procedure of handling system restrictions, constraint domination, to meet the system limitations. Results are looked over in parts and discussed. The proposed method was then compared with two previous methods from another study to exhibit the robustness of the suggested technique. Results have been found to be significant. R-NSGA-II can reduce the cost up to $4,853.04 a year compared with the SMODE-SF method and $1,795.8 a year compared to the MOEA/D-SF method.

ÖZ: Güç sisteminde son derece popüler ve temel optimizasyon problemlerinden biri ekonomik güç sevkidir. Klasik formdaki ekonomik sevk, ağ güvenliği kısıtlamalarını dikkate almadan yalnızca termal jeneratör içermektedir. Ancak bu sorunun ekonomik emisyon sevkiyatı gibi diğer biçimleri, emisyonun en aza indirilmesinin çevresel açıdan baskın olması nedeniyle daha fazla önem kazanmaktadır. Ayrıca, Yenilenebilir kaynakları şebekeye entegre etmek, stokastik doğası nedeniyle zorluklarla birlikte gelmektedir. Bu çalışmada, güneş, rüzgar ve küçük hidro ünite ile entegre ekonomik emisyon gücü sevk problemini ele almak için çok amaçlı bir algoritma geliştirilmiştir. Lognormal, Weibull ve Gumbel dağılımı güneş, küçük hidro ve rüzgar enerjisinin erişilebilir gücünü tahmin etmek için sırasıyla kullanılmaktadır. Çalışmanın amacı doğrultusunda, IEEE-30 test şebekesinin yapısında olan bazı geleneksel jenaratörler, farklı yenilenebilir enerji birimleriyle değiştirilmiştir. Gerilim sınırlaması, iletim hattının kapasiteleri, termik jeneratör tesisleri için yasak çalışma alanları ve sistemin kısıtlanması da göz önünde bulundurulmaktadır. Çok amaçlı gerçek kodlu baskın olmayan sıralama genetik algoritması II, bu çalışmanın problemine uygulanırken, sistem kısıtlamalarını karşılamak için kısıtlama derecesini ele almak için iyi bir prosedür içermektedir. Sonuçlar parçalar halinde incelenip, tartışılmaktadır. Önerilen yöntem daha sonra sunulan tekniğin sağlamlığını göstermek için başka bir çalışmada uygulanan iki yöntemle karşılaştırılmıştır. Sonuçlar anlamlı bulunmuştur. R-NSGAII, maliyeti SMODE-SF yöntemine göre, yılda 4,853,04 dolara, MOEA / D-SF yöntemine göre ise yılda 1,795,8 dolara kadar düşürülebilmektedir.
Master of Science in Electrical and Electronic Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Electrical and Electronic Engineering, 2021. Supervisor: Assoc. Prof. Dr. Reza Sirjani.
Keywords: Electrical and Electronic Engineering Department; Electric power systems--Wind Energy; Multi-objective optimization, Economic emission dispatch, renewable energy, stochastic modelling, microgrid